SINGLE MOM'S PARENTING PATTERN IN FORMING CHILDREN'S INDEPENDENCE AND THE ENVIRONMENT - Ariani, Meiliyah; Zulhawati; Hikmawatty, Sitti (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The pattern of single mother parenting has a difference with a family that is still intact, which of course will affect the development of children's independence. The purpose of the research is to explore the parenting patterns carried out by single parents, the obstacles faced by single parents in forming child independence, the efforts of single parents in fulfilling the rights of children and their environment, as well as parenting tips for single parents. The research method uses a descriptive qualitative approach. The subjects of this study are two single mothers who have children aged 5-6 years. Data collection techniques by observation, interviews and documentation. The research analysis uses interactive model analysis. The results of the study show that the parenting style provided by single mothers in shaping children's independence is a single parent parenting practice that applies a democratic parenting style, and a permissive parenting style. Children raised with democratic parenting have high independence while children raised with authoritarian parenting have less independence. Children's independence is also influenced by several factors, namely parental education, economy, employment, environment and religion in fulfilling children's rights is to build a good and harmonious relationship with children.